Effect of Picloram on Somatic Embryogenesis from Leaf-sheath Explants in Diploid Musa acuminata cv. Njalipoovan - Smitha, P.D.; Nair, Ashalatha S. (Plant Tissue Culture and Biotechnology, 2012)
Embryogenic callus was obtained from leaf sheath explants on MS supplemented with 16.56 μM picloram in Musa acuminata (diploid) cv. Njalipoovan (AB). Exogenous application of ascorbic acid on somatic embryogenesis at optimal level accelerated the conversion rate of the embryos. Shoot and root developed from the embryos on MS incubated in dark. Further growth of plantlets obtained on half strength of MS under light conditions. Regenerated plantlets showed 100% survival. Key words: Musa acuminata cv. Njalipoovan, Picloram, Somatic embryogenesis D. O. I. 10.3329/ptcb.v21i1.9612 Plant Tissue Cult. & Biotech. 21(1): 83-87, 2011 (June) - Short communication